Police Officers’ Qualified Immunity in Excessive Force Claims, Warrant Execution, and Warrantless Searches and Arrests: Tracing the Evolution of, and Stagnation in, U.S. Supreme Court Precedents - Braaten, Claire Nolasco (American journal of criminal justice, 2023)
We analyzed all U.S. Supreme Court cases as of June 6, 2020 where private complainants filed either a §1983 action or Bivens action against police officers who claimed the defense of qualified immunity (N = 29). Empirical analysis of qualified immunity claims involving excessive force, unlawful warrant executions, and unlawful warrantless searches and arrests reveal the Court’s growing trend of ruling in favor of police officers. In 10 out of 13 cases involving excessive force claims, three out of five unlawful warrant execution claims, and nine out of 10 unlawful warrantless searches and arrests claims, the Court granted police officers’ qualified immunity. The requirement for private complainants to identify a case where the Court ruled against the officer in similar circumstances makes it extremely difficult to defeat the defense of qualified immunity. The Court should reconsider its standard of proving "clearly established rights," an element of qualified immunity.